Environmental stress and socioeconomic status: Does parent and adolescent stress influence executive functioning in urban youth?. Issue 4 (2nd October 2019) - Mance, GiShawn A.; Grant, Kathryn E.; Roberts, Debra; Carter, Jocelyn; Turek, Carolyn; Adam, Emma; Thorpe, Roland J.
Abstract: This study examined whether parental and adolescent stress act as mediators between socio-economic status (SES) and adolescent executive functioning (EF) in urban youth. Two hundred and sixty-seven 6th–11th grade students (ages 11–16, 55.4% female; 49.1% Black/African American) attending racially and socioeconomically diverse schools in Chicago, Illinois, completed self-report measures on urban stress and EF. Parents of adolescents completed measures on parental chronic stress and demographic information on the family's socioeconomic status. Results indicated that parent stress was directly related to adolescent stress, while adolescent stress was directly related to behavior components of EF (i.e., emotion control, set shifting, and inhibition). Although parental stress was related to adolescent's ability to shift from one task to another, no relationship was found with adolescent's ability to modulate mood or delay impulsive behaviors. Implications for socio-ecological mental health interventions for youth residing in urban environments are discussed.